KEPERCAYAAN DAN KEPUASAN KONSUMEN DALAM TRANSAKSI ONLINE SHOP PERSPEKTIF EKONOMI ISLAM: (Studi Pada Jurusan Ekonomi Syariah STAIS Dharma Indramayu Pengguna Aplikasi Shopee) - Nuni Oktaviani; Hanof Hidayati (Khulasah : Islamic Studies Journal, 2025)
The problem discussed in this thesis is how consumer trust and satisfaction in online shop transactions among students majoring in Sharia Economics use the Shopee application. This can be seen from the fact that there are several students who are dissatisfied with online shop transactions in the Shopee application. The aim of this research is to determine and explain consumer trust and satisfaction in online shop transactions. The type of research that the author uses is descriptive qualitative research, namely by conducting direct interviews and online interviews with students of the Sharia Economics Department who are the primary data sources using tools, namely interview guides, cameras, while secondary data sources are obtained from documentation obtained from the results. study. The technique for analyzing data is qualitative descriptive analysis using data reduction, data presentation and drawing conclusions or verification. To ensure the validity of the data, triangulation is used. Based on the research results, it shows that consumer trust in online shop transactions with the Shopee application shows that by increasing trust in the form of assessments/testimonials from consumers and consumers who follow the Shopee online shop account, the use of the online buying and selling transaction system can increase. There are several students majoring in Sharia Economics who feel dissatisfied with the services provided by one of the online shop shops, namely in the form of slow response sellers when consumers want to make transactions and unclear information is not included in the description of one of the online shops. the shop. However, not all online shops on the Shopee application provide unsatisfactory services, there are those that provide services by increasing convenience in providing price discounts for goods/products, free shipping and goods/products that meet expectations, which makes consumers satisfied. So this causes the Shopee application to have a good reputation and creates consumer satisfaction to use it sustainably.